Unsaturated hydraulic properties of xerophilous mosses: towards implementation of moss covered soils in hydrological models - Voortman, B.R.; Bartholomeus, R.P.; van Bodegom, P.M.; Gooren, H.; van der Zee, S.E.A.T.M.; Witte, J.P.M. (Hydrological Processes, 2014)
Evaporation from mosses and lichens can form a major component of the water balance, especially in ecosystems where mosses and lichens often grow abundantly, such as tundra, deserts and bogs. To facilitate moss representation in hydrological models, we parameterized the unsaturated hydraulic properties of mosses and lichens such that the capillary water flow through moss and lichen material during evaporation could be assessed. We derived the Mualem-van Genuchten parameters of the drying retention and the hydraulic conductivity functions of four xerophilous moss species and one lichen species. The shape parameters of the retention functions (2.17<n<2.35 and 0.08<α<0.13cm